Inhaled Solvent Abuse Mimicking Chronic Inflammatory Demyelinating Polyradiculoneuropathy - Thulasirajah, Salini (Child Neurol Open, 2020)
Exposure to n-hexane or toluene-containing solvents such as glue or gasoline can produce clinical symptoms and neurophysiological findings that can mimic chronic inflammatory demyelinating polyneuropathy. The authors present a case of a boy with severe sensorimotor polyneuropathy with demyelinating features. Cerebrospinal fluid testing and magnetic resonance imaging spine did not show findings typical of chronic inflammatory demyelinating polyneuropathy. His lack of response to immunosuppressive therapy prompted a nerve biopsy which was instrumental in confirming a diagnosis of chronic organic solvent exposure, subsequently confirmed on history. This case highlights the importance of additional testing to ensure diagnostic certainty which allows appropriate treatment and/or disease management to be tailored appropriately including in this instance, the involvement of mental health counseling and avoidance of immunosuppressant medication.